Impact of Mental Health Problems on Self-Perceived Oral Health Needs in a Medicaid Population. (March 2015) - Boothroyd, Roger A.; Ware, Annie
The purpose of this study was to examine the prevalence of self-perceived oral health needs among Medicaid-enrolled adults with and without mental health problems and to identify factors predictive of enrollees' perceived oral health needs. The study involved a secondary analysis of 1, 721 respondents to the Florida Health Services Survey. Contrary to the previous research, the findings from this study indicated that respondents with mental health problems (52.9%) did not differ significantly in their dental needs compared to those who did not have mental health problems (49.3%). The results from a logistic regression suggested that after controlling for demographic characteristics, substance abuse problems and functional needs increased the likelihood of self-reported oral health needs, whereas the receipt of Supplemental Security Income (SSI) was associated with decreased dental needs. The prevalence of unmet dental needs among these respondents (i.e., 23%) supported the conclusion that a significant gap exists in the accessibility of oral health services among this population.